Analisis Framing Tayangan Kampanye Prabowo Gibran pada Program Prabowo Gibran Memang Istimewa - Astari, Irfany Wahyu (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to conduct a framing analysis of Prabowo-Gibran's campaign broadcasts on the program "Prabowo Gibran Memang Istimewa" using a qualitative method with reference to Erving Goffman's theory. The program is considered a strategic communication channel to shape the desired political image of the pair in the general election. Through framing analysis, this research examines how visual elements, narratives, and framing are effectively employed to shape a positive perception of Prabowo-Gibran. The study emphasizes the importance of unity, infrastructure development, personal image transformation, connection with the community, and conflict resolution as the main focal points of framing in the program. Using Goffman's theory, the research also identifies the roles of dramaturgy and self-presentation utilized in the campaign broadcasts, providing a profound understanding of how Prabowo-Gibran aims to position themselves in the eyes of the audience. The findings of this study are expected to contribute to understanding the dynamics of political communication in the digital era, particularly in the context of general election campaigns in Indonesia.